Comprehensive detection of pathogens in immunocompromised children with bloodstream infections by next-generation sequencing - Kazuhiro Horiba (Nature Portfolio, 2018)
Abstract Bloodstream infection (BSI) is a severe complication in immunocompromised patients. Next-generation sequencing (NGS) allows us to analyze comprehensively and quantitatively all microorganisms present in a clinical sample. Thirty-five pediatric patients (12 with BSI and 23 with suspected BSI/negative blood culture) were enrolled. Plasma/serum samples were used for sequencing and the results were compared with those from blood culture. Sequencing reads of bacteria isolated in blood culture were identified by NGS in all plasma/serum samples at disease onset. Bacteria isolated in blood culture were identical to the dominant bacteria by NGS in 8 of 12 patients. Bacterial reads per million reads of the sequence depth (BR) > 200 and relative importance values of the dominant bacteria (P1) > 0.5 were employed to determine causative pathogens. Causative pathogens were detected using these criteria in 7 of 12 patients with BSI. Additionally, causative bacteria were detected in the plasma/serum at 7 days before disease onset in two patients with catheter-related BSI. Causative pathogens, including virus, were identified in three patients with suspected BSI. Lastly, a total of 62 resistance genes were detected by NGS. In conclusion, NGS is a new method to identify causative microorganisms in BSI and may predict BSI in some patients.